One Health perspective on rabies: Incidence and risk factors in humans and livestock in northwest Ethiopia - Azalu, W.W.; Mekonnen, S.A.; Jemberu, Wudu T. (Elsevier, 2025)
Background: Rabies is a widespread disease affecting all warm-blooded animals. In developing countries, most human mortalities originate from rabid dogs. Every year, rabies is responsible for an estimated 60,000 human deaths worldwide, with 15 million people receiving rabies post-exposure prophylaxis (PEP), 4 million disability-adjusted life years, and 9 billion US$ dollars in economic losses. Incidence and associated risk factors of rabies in humans and livestock were conducted in North-West Ethiopia with the aim of quantifying the incidence and associated risk factors of rabies.